Estado nutricional y socio económico de los estudiantes de la Institución Educativa Nº 224 Indoamérica, Víctor Larco Herrera, junio - julio 2011 - Gallardo Palma, Jonathan Julio (2011)
Nutrition involves, in addition to the acquisition of nutrients, other phenomena such as digestion, absorption, distribution of nutrients in the body and especially their use by all body cells. All processes are performed involuntarily and unconsciously, as it does not depend on our willingness to absorb or no carbohydrates, lipids, proteins, vitamins and minerals your body needs, nor influence the subsequent fate. Inadequate feeding practices within the home have a negative effect on child health conditions on their ability to learn, communicate, think analytically, socialize effectively and adapt to new environments and people. The nutritional status of children is of great interest since they are the future of the country and therefore their nutritional status is the result of multiple factors which can include economic, social and cultural rights as an important consideration to assess the state nutrition of children under 5 years.